2015
DOI: 10.1177/0957650914566895
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated solar power: Recent developments and future challenges

Abstract: With the mass-manufacture and resulting low cost of silicon photovoltaics driven by Western government subsidy schemes and large-scale manufacturing, concentrated solar power for electricity generation is now at a turning point. The present cost of mirrors, lenses, support structure and plant for concentrated solar thermal power, and of the highefficiency multi-junction cells, concentrating optics and two-axis tracking systems for concentrated photovoltaic power, has made operational concentrated solar power p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…This point is especially advantageous in arid regions with appropriate solar resources. To get those efficiencies quite high turbine inlet temperatures have to be reached in the solar receivers, about 800 -1000°C [8,9,10,11]. Several experimental prototypes have shown that this is feasible using ceramic materials in central tower volumetric receivers or other alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…This point is especially advantageous in arid regions with appropriate solar resources. To get those efficiencies quite high turbine inlet temperatures have to be reached in the solar receivers, about 800 -1000°C [8,9,10,11]. Several experimental prototypes have shown that this is feasible using ceramic materials in central tower volumetric receivers or other alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…25 indicates, using the Eqs. (4,19,20,21), With the η pet to be the Petela factor for exergetic efficiency, (25) …”
Section: Preliminary Results Of This Analysismentioning
confidence: 99%
“…Solar energy is one of the most reliable choices among the renewable resources because this energy source can be converted into useful heat or electricity [4][5][6][7]. Numerous applications use solar energy for covering their energy needs.…”
Section: Introductionmentioning
confidence: 99%
“…S3). Concentrated solar power (CSP) technologies are extensively studied in the literature (32)(33)(34). The proposed SWP cycle is a central tower and direct steam cycle-type CSP plant.…”
Section: Benefits Relative To the Standalone Processesmentioning
confidence: 99%